An investigation into the disaster risk reduction (DRR) efforts in Gutu District (Zimbabwe): a focus on drought early warning systems - Shamano, Nicholas (University of the Free State, 2010)
The dynamic nature of vulnerability coupled with increasing volatility of climatic and environmental conditions, characterised by more frequent and extreme hazards, disaster management practitioners, decision makers and communities, especially those at risk, need to take action to protect vulnerable people and environments (UN/ISDR, 2002; 2006a; 2006b). In recent years, poor communities have had to bear .the brunt of the hazards. Gutu district in Masvingo Province of Zimbabwe, which is the study area of this thesis, has in recent times experienced more frequent droughts and floods. This research aimed to determine the Disaster Risk Reduction activities, particularly Early Warning, existing and being implemented in Gutu District. From the findings, the research then ascertained if the utilisation of more and varied EW can improve ORR efforts in Gutu. The research focused on a rural and inherently drought-prone district. In addition to review of existing literature, the research also collected primary data. This involved use of Participatory Rural Appraisal techniques such as Focus Group Discussions, In-depth interviews and simple observations. These techniques enabled the researcher to get insightful explanations into the prevailing situation, trends, processes and decisions that occur within the context of the study. The various data collection methods and multiple respondents enabled triangulation of the findings. Merging the literature review and field research with the thesis proposition that more ORR efforts, especially EW, can significantly reduce disaster risk and impacts, it was found that there are ORR and EW established and ongoing activities in Gutu. However, these are not adequate and more ORR initiatives, including EWs are, needed to significantly reduce the vulnerability of the communities to hazards. The study established that the drought hazard remains the biggest hazard threatening the lives and livelihoods of the Gutu community. Other notable hazards include the HIVand AIDS pandemic, flooding which sometimes alternate with drought, diarrhoeal and water-borne diseases, crop and livestock diseases and environmental degradation. There are also marked challenges in the quest to reduce community vulnerability. These need to be addressed while, at the same time, ORR efforts can be scaled up. EWs are one of the key ORR strategies the community felt could be effectively and efficiently utilised in the district. In line with this, the study offers recommendations for ORR and Early Warnings for policy and practice as well as future research.
Dissertation (M.Disaster Management (Disaster Management Training and Education Centre for Africa))--University of the Free State, 2010
Keywords: Droughts -- Zimbabwe; Climate change; Disaster risk reduction; Drought and floods; Disaster management